Endothelial Dysfunction in Systemic Lupus Erythematosus and Systemic Sclerosis: A Common Trigger for Different Microvascular Diseases - Moschetti, Liala; Piantoni, Silvia; Vizzardi, Enrico; Sciatti, Edoardo; Riccardi, Mauro; Franceschini, Franco; Cavazzana, Ilaria (Frontiers in Medicine, 2022)
Systemic autoimmune diseases are a group of disorders featured by humoral and cell-mediated immune responses against several self-molecules. Despite the fact that diagnostic methods and therapies have been significantly improved in the last years, affected patients show an excess of cardiovascular mortality if compared with the general population. This review describes the complex interplay between inflammation, vasculopathy and fibrosis that involve the heart and peripheral small vessels, leading to endothelial stiffness, vascular damage and early ageing in patients with Systemic Lupus Erythematosus and Systemic Sclerosis. In addition, we provide a complete overview on the new techniques which are used for the evaluation of endothelial dysfunction in a preclinical phase, which could represent a new approach in the assessment of cardiovascular risk in these patients.